Measurement of charged and neutral kaons in Ar+Sc collisions at the NA61/SHINE experiment - Susa Tatjana (EPJ Web of Conferences)
NA61/SHINE is a large-acceptance fixed-target experiment conducted at the CERN SPS. The experiment has measured charged kaon production in 0-10% central Ar+Sc collisions at beam momenta of 13A, 19A, 30A, 40A, 75A, and 150A GeV/c. In this report, we present the measurements of KS0 production and charged-to-neutral kaon ratio in 0-10% central Ar+Sc collisions at 75A GeV/c. The results are compared to the charged and neutral kaon production in other collision systems measured by NA61/SHINE, as well as to model predictions and data from other experiments.